Prevalence of urinary shedders and characterization of pathogenic Leptospira among cattle population in Tamil Nadu ‑ Implications for control - Senthilkumar, K.; Ravikumar, G.; Parthiban, Aravindh Babu R. (Veterinaria Italiana, 2022)
Bovine leptospirosis causes jaundice, mastitis, infertility, abortion, and death of infected animals. This research aimed to study the status of urinary shedders of pathogenic Leptospira among the cattle population and identify the infecting serogroup circulating in the state of Tamil Nadu (India). A total of 305 blood and 305 urine samples were collected from organized farms (n = 44), individually housed animals (n = 81) and animals from the slaughterhouse (n = 180). Microscopic agglutination test was carried out to detect anti‑leptospiral antibodies. Dark‑field microscopic examination and culture of urine were done to detect and isolate the Leptospira. The isolated Leptospira were identified by cross‑agglutination test and gene sequencing. PCR and real‑time PCR were carried out to detect leptospiral genomic DNA in urine samples to detect the shedders. The anti‑leptospiral antibodies were detected in 6.2% of animals. The Leptospira genomic DNA was detected in 9.2% (28/305) of urine samples. Of the 28 Leptospira positive urine samples, 39.2% were from animals with clinical signs suggestive of leptospirosis and 60.8% Leptospira positive samples were from slaughterhouse animals. The Leptospira isolated were identified as Leptospira interrogans serogroup Sejroe and Hebdomadis. The present study demonstrates the need to include leptospirosis in cattle health surveillance programmes to prevent leptospirosis and renal carriage by vaccination.